Impacts of jellyfish on marine cage aquaculture: an overview of existing knowledge and the challenges to finfish health. (2nd April 2021) - Clinton, Morag; Ferrier, David E K; Martin, Samuel A M; Brierley, Andrew S
Abstract: Gelatinous plankton present a challenge to marine fish aquaculture that remains to be addressed. Shifting plankton distributions, suggested by some to be a result of factors such as climate change and overfishing, appear to be exacerbated by anthropogenic factors linked directly to aquaculture. Fish health can be negatively influenced by exposure to the cnidarian hydrozoan and scyphozoan life stages commonly referred to as "jellyfish". Impact is particularly pronounced in gill tissue, where three key outcomes of exposure are described; direct traumatic damage, impaired function, and initiation of secondary disease. Cnidarian jellyfish demonstrated to negatively impact fish include Cyanea capillata, Aurelia aurita, and Pelagia noctiluca . Further coelenterates have also been associated with harm to fish, including sessile polyps of species such as Ectopleura larynx . An accurate picture of inshore planktic exposure densities within the coastal environments of aquaculture would aid in understanding cnidarian species of concern, and their impact upon fish health, particularly in gill disease. This information is however presently lacking. This review summarises the available literature regarding the impact of gelatinous plankton on finfish aquaculture, with a focus on cnidarian impact on fish health. Present strategies in monitoring and mitigation are presented, alongside identified critical knowledge gaps.